2017
DOI: 10.1097/md.0000000000007812
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns among various age and gender groups of trauma patients in southern Iran

Abstract: Administrative data from trauma referral centers are useful sources while studying epidemiologic aspects of injuries. We aimed to provide a hospital-based view of injuries in Shiraz considering victims’ age and gender, using administrative data from trauma research center.A cross-sectional registry-based study of adult trauma patients (age ≥15 years) sustaining injury through traffic accidents, violence, and unintentional incidents was conducted. Information was retrieved from 3 hospital administrative databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
6
23
1
5
Order By: Relevance
“…Among the population of this study, 8.3% of traffic accident victims died. Other studies have shown lower hospital mortality rates, ranging from 1.0 in various types of trauma [34] to 3.9% only among victims of traffic accidents [35]. The death rates resulting from traffic accidents decreased in some countries [36,37], including Brazil [38], however, among victims of external causes, traffic accidents were responsible for the majority of deaths [25,39].…”
Section: Discussionmentioning
confidence: 99%
“…Among the population of this study, 8.3% of traffic accident victims died. Other studies have shown lower hospital mortality rates, ranging from 1.0 in various types of trauma [34] to 3.9% only among victims of traffic accidents [35]. The death rates resulting from traffic accidents decreased in some countries [36,37], including Brazil [38], however, among victims of external causes, traffic accidents were responsible for the majority of deaths [25,39].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, é expressiva a publicação de investigações [7][8][9][10]12,[14][15][16][17][23][24][25][26][27][28][29][31][32][33][35][36][43][44][45][46][47][48][49][50] que apontam para uma relação entre morbidade e mortalidade por queda e idade avançada, reforçando a importância de se pesquisar este mecanismo de trauma na população de idosos.…”
Section: Variáveis Independentesunclassified
“…A presente investigação identificou predomínio do sexo masculino (57,8%) entre as vítimas fatais por queda. Em comparação a outros estudos, alguns mostram prevalência de homens [8][9]17,27,[30][31]33,36,43 enquanto que outros retratam maior frequência de mulheres 10,24,29,32,35 .…”
Section: Variáveis Independentesunclassified
See 2 more Smart Citations